The Diffusion of M-Pesa in Developing Countries: Convergence Program Lead Vodafone Albania Sh.a, Tirane, Albania - Bregu, Elvis; Anamali, Armela; Shosha, Bitila (European Journal of Economics and Business Studies, 2019)
The purpose of this study is to investigate whether this kind of innovative service was successful in all developing countries. Prior to the introduction and implementation of M-Pesa, people used a variety of formal and informal channels to save or send money to others. It is supposed that through mobile money technology, the population currently out of the reach of financial services will be integrated as formal players into the market and that informal ways of transferring money will be reduced (Jenkins, 2008). Financial inclusion is an issue that has gathered a lot of attention among policymakers and researchers and is referred to as a process that guarantees ease on access, availability and also the usage of banking services for all householders of a country (Sarma, 2010). Without doubt, the introduction of M-Pesa in Kenya has deeply changed the way through which transactions occur. Based on the review of the literature but also the case-studies on the application of M-Pesain Albania and other countries, at the end of the paper we give some important conclusions.
Keywords: M-Pesa, mobile money, developing countries, case-study, Kenya, Eastern Europe